Wellness Programming in Collegiate Athletics: A Movement Toward Balance - Goodloe, Nancy R. (My University, 1989)
This is a commentary on whether athletic participation leads to positive personal development of athletes, suggesting six dimensions of wellness to focus programming on for athletes.
Keywords: well-being